Nutrient Management Strategies to Control Broomsedge Infestation and Improve Yield and Quality of Tall Fescue Hayfields - Junior I. Yasuoka; Dale Helwig; Wendie Powell; Jaymelynn K. Farney; Gretchen F. Sassenrath; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
A study in tall fescue hayfields infested with broomsedge and bluestem was conducted at four locations in southeast Kansas. The purpose of this study was to evaluate how phosphorus, nitrogen, and potassium fertilization affect yield, forage quality, and broomsedge/bluestem control in tall fescue hayfields. This trial will be repeated in 2023.
Keywords: weed control; biomass; nitrogen; phosphorus; potassium